Diagnostic Workup of Acute Myeloid Leukemia: What Is Really Necessary? An Italian Survey - Voso, Maria Teresa; Ferrara, Felicetto; Galimberti, Sara; Rambaldi, Alessandro; Venditti, Adriano (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is a heterogeneous disease with a wide variety of clinical presentations, morphological features, and immunophenotypes. The diagnostic approaches to AML that are adopted in Italy have been explored using an online Delphi-based process to expand the global discussion on mandatory tests for the correct diagnosis and, consequently, for optimal management of AML in clinical practice. The final results of the panel of Italian hematologists involved in this work highlight the importance of genetic evaluation for classification and risk stratification and firmly establish that karyotyping, fluorescence in situ hybridization in cases with non-evaluable karyotype, and molecular tests must be performed in every case of AML, regardless of age. Obtaining clinically relevant genetic data at diagnosis is the basis for the success of patient-tailored therapy. The Italian specialists also confirm the role of multidisciplinary diagnostics for AML, now mandatory and expected to become more important in the future context of “precision” medicine.